THE QUALITY FUNCTION DEPLOYMENT AND THE CUSTOMER SATISFACTION. THE CASE OF UNIVERSITIES - Ida Verna (European Scientific Journal, ESJ, 2014)
This research aims at applying the Quality Function Deployment methodology to a university course in accounting. The final objective is to make more competitive university programs by applying a quality methodology able to define the real customer needs. In particular, in this paper, the QFD allows us to assess the learning needs of students in an accounting course and translate them into educational strategies (specific techniques) able to satisfy such needs. In conclusion, we evaluated the effectiveness of the didactic strategies adopted by professors of the accounting course, in perspective of the customer (students) training needs. The results allow us to define "the right things to do for the first time", a significant support for the improvement of university courses.